Effect of pre-chilling and environmental factors on breaking seed dormancy and germination of three foxtail species - Vajihe AMINI; Faezeh ZAEFARIAN; Mohammad REZVANI (Acta Agriculturae Slovenica)
The effect of wet and dry pre-chilling duration, pH, osmotic stress, salt stress and planting depth on seed germination and seedling emergence of three foxtail species (Setaria glauca, S. verticillata and S. viridis) was investigated in a series of laboratory and greenhouse experiments. Both wet and dry pre-chilling for 45 days promoted seed germination of S. glauca compared with the control. Pre-chilling was not significantly effective in seed dormancy breaking of S. viridis and S. verticillata. The maximum germination of foxtails (S. verticillata, S. viridis) was obtained when seeds were treated with pH 7 buffer solution. Increasing of osmotic and salt stress decreased seed germination of foxtails. Setaria verticillata seed germination was more tolerant than those of S. glauca and S. viridis to high water stress condition. Setaria glauca and S. verticillata seed germination were more tolerant to high salinity stress than S. viridis. Seedling emergence decreased with increasing the burial depth and no germination observed at 8 cm soil depth.